The clinical characteristics of women with recurrent implantation failure. (July 2013) - Coughlan, C.; Yuan, X.; Nafee, T.; Yan, J.; Mariee, N.; Li, TC
<x xml:space="preserve">Abstract</x> Recurrent implantation failure (RIF) refers to failure to conceive after three or more in vitro fertilisation (IVF) or embryo transfer cycles. Implantation failure may be due to embryo or uterine factors. There are many controversies surrounding the investigation and management of this condition. The aim of our study was to describe the clinical characteristics and the outcome of investigations of a group of women with recurrent implantation failure. A total of 111 couples with RIF were managed in a dedicated clinic and investigated according to a clinic protocol. The frequency of abnormal investigations were as follows: high (≥ 10 IU/l) FSH, 14/107(13%); high free androgen index 6/78(8%); abnormal hysteroscopic findings 7/45(16%); hydrosalpinges 8/33(24%); persistently elevated ACA or tested positive for lupus anticoagulant 19/108 (18%); abnormal karyotype analysis 3/101(3%); hyperprolactinaemia 1/79(1%); abnormal thyroid function 4/100(4%) and tested positive for thyroid peroxidase antibody 10/104(10%). Specific treatments according to the results of investigation produced a live birth rate of 29%. It was concluded that the findings should help practitioners to construct suitable investigation protocols for the initial management of this condition.